Safety, tolerability and pharmacokinetics of ASC10, a novel oral double prodrug of a broad-spectrum antiviral agent, β-d-N4-hydroxycytidine: results from a randomized, double-blind, placebo-controlled phase 1 study in Chinese healthy subjects - Liu, Jian; Zhao, Qingwei; Zhai, You; Wu, Xia; Kai, Jiejing; Ruan, Jie; Wu, Minglan; Wu, Meijia; Zhou, Zhuojun; Yan, Yuemei; Wu, Jinzi J; Qiu, Yunqing (Expert opinion on investigational drugs, 2024)
Considering the rise of new SARS-CoV-2 variants that have reduced the efficacy of COVID-19 vaccines, the development of new antiviral medications for the disease has become increasingly necessary. In this study, ASC10, a novel antiviral prodrug, was studied in a phase 1 trial in healthy Chinese participants. Part 1 involved 60 participants, receiving 50-800 mg ASC10 or placebo twice daily for 5.5 days. Part 2, with 12 participants, explored ASC10 dosing in the fed/fasting states. ASC10-A, the main pharmacologically active metabolite, rapidly appeared in plasma (T : 1.00-2.00 h) and decreased (t : 1.10-3.04 h) without accumulation. The C and area under the plasma concentration - time curve (AUC) of ASC10-A increased dose-dependently (50-800 mg BID) over 5.5 days, with no accumulation. The T was slightly delayed in the fed state; however, the C and AUC were similar between the fed and fasting states. Adverse events (AEs) were comparable (ASC10/placebo, 66.7%) and mostly mild (95%). ASC10 was demonstrated to be safe and well tolerated and exhibited dose-proportional exposure and minimal food effects. www.clinicaltrials.gov identifier is NCT05523141.